SPM to UTHM: An Animated Guide to Your Tertiary Education Journey (HALATUJU) - Ibrahim, Zuraida; Idrus, Mirza; Mohd Noor Nizam, Ahmad Imranul Muzammel; Muhamad Zamri, Muhamad Afham Aqil (Multidisciplinary Applied Research and Innovation, 2025)
This project focuses on SPM graduates, with a primary target audience of students who have completed their SPM exams. It highlights the declining numbers of students continuing their studies at the university level. Several factors contribute to this trend. Some students perceive university education as a waste of time that does not guarantee a bright future and the influence of content creators nowadays encourages students to ignore higher education, leading to less exposure to the benefits of enrolling in a university. This project aims to create an effective animation video for SPM graduate students that guides them in deciding on their future education plan. The animation video aims to attract the interest of SPM graduate students in pursuing further their education and provides information about the diploma programs offered at UTHM. This research is important for spreading information about tertiary education in universities and its benefits as well as encouraging SPM graduate students to continue their studies. This research found that 51% of SPM graduates intend to pursue further education, 39% plan to seek employment and 10% have no specific plans according to UCSI Poll Research Centre[1]. The chosen methodology for this research involves quantitative research, analysis and Internet reading. The authors collect relevant data to address this issue. The project follows three basic phases in creating animation: pre-production, production and post-production.